PRIMARY AND SECONDARY NOMINATION: DIFFERENTIATION OF CONCEPTS (World Bulletin of Social Sciences, 2023)
This article deals with the differentiation of concepts: primary and secondary nomination. It studies the starting point for research on nomination, that is,socalled primary nomination, which, in fact, is a rare occurrence in modern languages, since today languages are replenished through borrowings or secondary nomination, which means the use in the act of nomination of a phonetic aspect of a unit already existing in the language as a name for new object or phenomenon.